The Influence Of Free Cash Flow, Profitability and Growth Opportunity On Dividend Policy - I Gede Agus Sumartana; Sayu Ketut Sutrisna Dewi (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
Dividends are one of the returns expected by shareholders apart from capital gains. Dividend distribution to investors gives a positive signal to investors for making investment decisions. The aim of this research is to analyze and explain the influence of free cash flow, profitability and growth opportunity on dividend policy. The number of samples in this research was 33 mining sector companies in 2018-2022. Data collection uses non-participant observation methods. The data analysis technique used is multiple linear regression analysis. The results of the analysis show that free cash flow has a significant positive effect on dividend policy, profitability has a significant positive effect on dividend policy and growth opportunity has a significant negative effect on dividend policy. The theoretical implication of this research is to provide knowledge and strengthen dividend policy theories related to free cash flow, profitability and growth opportunity. The practical implication of this research is that information on profitability and free cash flow produced by the company is used by the company to determine future investment directions or distribute dividends to investors as a form of good perception in the eyes of investors.